PENGARUH KUALITAS PRODUK MURABAHAH TERHADAP TINGKAT PENJUALAN PERUMAHAN - Yasin, Muhammad; Mariana, Mariana (At-Tawazun, Jurnal Ekonomi Syariah, 2022)
This study aims to determine how much influence the quality of murabahah products has on the level of housing sales in the Jasa Cipta Graha Investama Cooperative, Sangatta East Kutai. The variables used are the quality of murabahah products as the independent variable and the level of housing sales as the dependent variable. This type of field research (field research) using a quantitative approach. The population of this study were all customers in the Jasa Cipta Graha Investama Cooperative, Sangatta Kutai Timur, with 41 respondents. The data collection method used is a questionnaire (questionnaire), observation and documentation. The analysis used includes validity test, reliability test and linear regression analysis with the help of SPSS software program. The results of hypothesis testing indicate that the quality of murabahah products has a significant effect on the level of housing sales in the Jasa Cipta Graha Investama Sangatta Cooperative, with the Fcount value of 32,695 with a significance/probability level of 0.000 <0.05. The contribution of the murabahah product quality variable has an influence on the level of housing sales at the Jasa Cipta Graha Investama Cooperative, Sangatta Kutai Timur by 45.6% while the remaining 54.4% is influenced by other variables.